Ihtikar Dan Permasalahannya Dalam Perspektif Hukum Islam - Lukman Hakim (IAI Darussalam, 2016)
Ihtikar is one business practice that it is immoral and inhumane. Olehkarena it, this kind of business practice is harmful will give rise effect to people's lives in general. This behavior is the law prohibited, although perhaps prohibited level would have been different and depends on qorinahnya, whether it involves dhoruriyat, hajjiyat, and tahsiniyat. It is also closely related to the monopoly and the resulting dhoiq for the community. Muhtakir Allah is inflicted with leprosy, accursed, and bankruptcy